2018
DOI: 10.1017/s0007114518000399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional supplement on bone marrow-derived mesenchymal stem cells from aplastic anaemia

Abstract: Aplastic anaemia (AA) is characterised by pancytopenia resulting from a marked reduction in haemopoietic stem cells (HSC). The regulation of haemopoiesis depends on the interaction between HSC and various cells of the bone marrow (BM) microenvironment, including BM-derived mesenchymal stromal cells (BMSC). The purpose of this study was to analyse the biological effect of nutritional supplement (NS), a dietary supplement consisting of thirty-six compounds: amino acids, nucleotides, vitamins and micronutrients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The mechanism underlying IFN-γ-inhibited hematopoiesis was complex, involving several ways for the occurrence of AA. Several investigations indicated that IRF - 1 gene could activate not only the expression of IFNs but also show the activity of tumor suppressor, which can inhibit cell proliferation as an anti-cancer effect ( 11 - 13 ); also, the micro-expression of IRF-1 inhibited the cell proliferation ( 3 ). These studies showed that IRF - 1 gene plays a major role in the IFN-γ-inhibited cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying IFN-γ-inhibited hematopoiesis was complex, involving several ways for the occurrence of AA. Several investigations indicated that IRF - 1 gene could activate not only the expression of IFNs but also show the activity of tumor suppressor, which can inhibit cell proliferation as an anti-cancer effect ( 11 - 13 ); also, the micro-expression of IRF-1 inhibited the cell proliferation ( 3 ). These studies showed that IRF - 1 gene plays a major role in the IFN-γ-inhibited cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a nutraceutical compound, methylsulfonylmethane promoted MSC differentiation, chondrogenesis, and preosteoblast formation [303]. In addition, a mixture of 36 nutrients promoted proliferation and osteogenic differentiation and inhibited adipogenesis of BMSCs from rats with aplastic anemia [304]. Indeed, piceatannol inhibited adipogenic activity in human MSC-derived adipocytes through PPARγ downregulation [305].…”
Section: Pharmacological and Nutraceutical Interventionsmentioning
confidence: 99%